Bta-miR-149–3p suppresses inflammatory response in bovine Sertoli cells exposed to microcystin-leucine arginine (MC-LR) through TLR4/NF-kB signaling pathway - Xue, Wang; Tianrun, Wang; Jiaqi, Yao; Xin, Li; Ruxue, Deng; Peng, Zheng (Ecotoxicology and environmental safety, 2024)
This study explored the regulatory role of bta-miR-149–3p in the inflammatory response induced by microcystin-leucine arginine (MC-LR) exposure in bovine Sertoli cells. The research endeavored to enhance the comprehension of the epigenetic mechanisms underlying MC-LR-induced cytotoxicity in Sertoli cells and establish a foundation for mitigating these effects in vitro. In this study, we elucidated the regulatory mechanism of bta-miR-149–3p in the MC-LR-induced inflammatory response by verifying the target gene of bta-miR-149–3p through luciferase assays and treating the cells with a bta-miR-149–3p inhibitor for 24 h. The results demonstrate that nuclear factor κB (NF-κB) acts as a downstream target gene of bta-miR-149–3p, which inhibits the MC-LR-induced inflammatory response in bovine Sertoli cells. This inhibition occurs by regulating the downregulation of tight junction constitutive proteins of the blood-testis barrier (BTB) through the suppression of the TLR-4/NF-κB signaling pathway (p < 0.05) and the up-regulation of the adhesion junction protein β-catenin (p < 0.05). Notably, MC-LR exposure resulted in the up-regulation (p < 0.05) of inflammatory cytokines (IL-6, IL-1β, and NLRP3) and the down-regulation (p < 0.05) of BTB tight junction constitutive proteins (ZO-1, Occludin) in Sertoli cells. Furthermore, the BTB constitutive protein ZO-1 exhibited significant down-regulation in Sertoli cells pretreated with the bta-miR-149–3p inhibitor compared to controls (p < 0.05), while Occludin showed no significant difference from CTNNB1 (p > 0.05). In summary, our findings suggest that bta-miR-149–3p suppresses the MC-LR-induced inflammatory response and alterations in the expression of BTB proteins in bovine Sertoli cells by inhibiting the TLR-4/NF-κB signaling pathway. •This study explored the regulatory role of bta-miR-149–3p in the inflammatory response induced by MC-LR exposure in bovine Sertoli cells.•NF-κB acts as a downstream target gene of bta-miR-149–3p in bovine Sertoli cells.•Bta-miR-149–3p suppresses the MC-LR-induced inflammatory response by inhibiting the TLR-4/NF-κB signaling pathway.•The research endeavored to enhance the comprehension of the epigenetic mechanisms underlying MC-LR-induced cytotoxicity in Sertoli cells.